2022
DOI: 10.1177/1351010x221131390
|View full text |Cite
|
Sign up to set email alerts
|

Single-number values versus subjective judgment of airborne sound insulation in dwellings

Abstract: There is a long history of adapting airborne sound insulation in buildings to the actual needs. A first pan-European work was published with COST Action TU0901: Integrating and Harmonizing Sound Insulation Aspects in Sustainable Urban Housing Constructions in which the differences between the sound insulation measure and the standard sound level difference were documented. Furthermore, ISO 16283-1: Field measurement of sound insulation in buildings and of building elements—Part 1: Airborne sound insulation sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Note, however, that once uncertainty is incorporated in building B3, the D nT,w decreases from 38 dB to 36.5 dB, with a confidence level of 95%. These deviations with respect to the standard may contribute to noise-related disturbances between dwellings, potentially impacting the health of occupants [11].…”
Section: Overall Levelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Note, however, that once uncertainty is incorporated in building B3, the D nT,w decreases from 38 dB to 36.5 dB, with a confidence level of 95%. These deviations with respect to the standard may contribute to noise-related disturbances between dwellings, potentially impacting the health of occupants [11].…”
Section: Overall Levelsmentioning
confidence: 99%
“…The researchers discovered a notable association between airborne noise annoyance and the apparent sound transmission class (ASTC), a single numerical value used to measure sound insulation based on the ASTM E336-20 standard [10]. Similarly, Rauscher et al (2023) [11] conducted a comparable perceptual study and found a significant correlation between perceived loudness and the D nT,w . The findings suggested that these single numerical values could effectively represent the perceived level of airborne sound insulation.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed in which cases stationary sounds with the same average Fourier spectrum are perceived louder compared to non-stationary sounds. Frescura and Lee 20 investigated noise annoyance by neighbours’ noise in wooden residential buildings.20 Neubauer 21 and Rauscher et al 22 performed a study that compared existing SNQs for in situ assessment: weighted standardized level difference ( D nT, w ) and weighted normalized apparent sound reduction index ( R ′ w ). The study, which was based on three sound stimuli and six wall types, has shown a better correspondence of D nT, w with the subjective impression of airborne sound insulation than the quantity R′ w .…”
Section: Introductionmentioning
confidence: 99%